Event management system / Chin Lee Kian - Chin , Lee Kian (2004)
As we all know nowadays, people like holding or celebrating events in restaurants ballrooms, hall and others. Hence, I came out with this system, Event management system, which is suitable for both hotel and restaurant businesses in order to manage vents systematically and help to ease tedious tasks for the users. This system will allow people to reserve the place and food to hold events. This is a real-time and online application. People can reserve places through phone, walk-in or Internet. For the local environment, a booking application will be developed to allow reservation through phone or walk-in. This is to bring conveniences to those customers that are not familiar with the use of internet. Operators are allowed to send reminders to the customers and view schedule generated by the system to avoid double booking. Besides this system will help to print out invitation cards to the guests invited and allocate scats for them. Meanwhile, administrators can add or edit operators' details, company profiles, facilities details, approve events and view reports. For the online environment, only members can log in to the web site to reserve rooms, meal packages, publish events and send email to their guests. For non-registered member, they can browse through the web site for information about the upcoming events and the facilities provided by the company. They may choose to register as a valid member too. To ensure the system efficiency and attempt to meet the user needs, existing Event management system have been reviewed to do analysis on user requirements. synthesis of the proposed system is made based on this analysis. The methodology, waterfall model with prototyping, has been chosen to develop this system. Functional and non-functional requirements for this system are stated clearly for tile purpose or controlling and monitoring in the future. The basic concept or the system was reviewed to find out the most suitable technologies in order to develop this system. Java, JSP, SQL Server 2000 and other helpful development tools are chosen to develop this system. System architecture design, system functionality design, database design and user interface design were used to develop prototyping for the system before the development of the complete system.